2022
DOI: 10.1101/2022.07.25.22277569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of post-vaccination fever with specific antibody response to SARS-CoV-2 BNT162b2 booster and no significant influence of antipyretic medication

Abstract: Background: A SARS-CoV-2 mRNA vaccine booster elicits sufficient antibody responses that protect against COVID-19, whereas adverse reactions such as fever have been commonly reported. Associations between adverse reactions and antibody responses have not been fully characterized, nor has the influence of antipyretic use. Methods: This is a prospective observational cohort study in Japan, following our prior investigation of BNT162b2 two-dose primary series. Spike-specific IgG titers were measured for SARS-CoV-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Unlike animal models of SARS-CoV-2 infections ( 17), several prior studies observed no detriment to post-vaccination antibody responses by analgesic use, but differed on whether their use was in fact associated with elevated titers (18)(19)(20). A causal positive relationship between analgesic use and antibody levels would be unexpected, but in theory might be explained by the suppression of inflammation that is detrimental to B cell responses (24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike animal models of SARS-CoV-2 infections ( 17), several prior studies observed no detriment to post-vaccination antibody responses by analgesic use, but differed on whether their use was in fact associated with elevated titers (18)(19)(20). A causal positive relationship between analgesic use and antibody levels would be unexpected, but in theory might be explained by the suppression of inflammation that is detrimental to B cell responses (24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
“…It remains unclear whether these same inhibitory effects are seen in humans after mRNA vaccination and how different classes of painkillers impact the antibody response. Several prior studies have suggested minimal or even positive impacts of antipyretic use on antibody responses (18)(19)(20). Further analysis of their impact, independent of symptoms and inflammation, as well as subgroup analyses on variables such as age, vaccine type, and the class of analgesics, would be valuable to help interpret these findings.…”
mentioning
confidence: 97%